(untitled) (Research, Society and Development, 2023)
This article aims to problematize Laurentino Gomes’ social position within the social memory of slavery. We will cross-reference the analysis of the book Escravidão: Do primeiro leilão de cativos em Portugal até a morte de Zumbi dos Palmares (2019), published by Globo Livros, with the recent social historiography of slavery. Gomes’ book (2019) was the first one in a trilogy on the subject of slavery. We also consider the blindfolding of the author’s last trilogy that dealt with Brazilian imperial political history, in which we observe a great public interest in his writing. In order to problematize the position that Gomes occupies in Brazilian society and from where he discusses about slavery, we start from the question of Djamila Ribeiro (2019): “Within this colonization project, who were the subjects authorized to speak?”. We understand that Gomes as a white man who occupies a place of power in Brazilian journalistic and editorial writing has discursive authority and he uses it to sell his books. Based on a historiographical review, analysis of interviews and Gomes’ positions on digital networks, we will discuss the author’s social position, in addition how his hegemonic narrative disputes the construction of a social memory of slavery. To analyze the social memory of slavery we will use Ricoeur’s (2007) concepts of "duty of memory" and "duty of justice".